2007
DOI: 10.1002/elan.200703892
|View full text |Cite
|
Sign up to set email alerts
|

Silicomolybdate‐Doped PEDOT Modified Electrode: Electrocatalytic Reduction of Bromate and Oxidation of Ascorbic Acid

Abstract: Electrically conducting poly(3,4-ethylenedioxythiophene) (PEDOT) film doped with silicomolybdate (SiMo 12 O 40 4À or SiMo 12 ) was synthesized by electrochemical polymerization. The synthesized film is capable of fast charge propagation during redox reactions in strong acid medium 0.2 M H 2 SO 4 solution. The modified electrode was used towards reduction of bromate and successfully employed as an amperometric sensor for bromate and also above modified electrode was investigated for ascorbic acid oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Oral administration of BrO 3 − in drinking water to rats and mice induce significant increased incidences of mesotheliomas of the peritoneum, renal and thyroid cell tumors. In addition, experiments confirmed that BrO 3 − has the acute effects on the auditory function of animals and humans (Balamurugan and Chen 2007). Because of carcinogenic characters of bromate, the World Health Organization (WHO) and the United States Environmental Protection Agency (USEPA) have recommended a maximum acceptable bromate concentration of 10 μg/L (0.078 μM) (Xie et al 2008).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Oral administration of BrO 3 − in drinking water to rats and mice induce significant increased incidences of mesotheliomas of the peritoneum, renal and thyroid cell tumors. In addition, experiments confirmed that BrO 3 − has the acute effects on the auditory function of animals and humans (Balamurugan and Chen 2007). Because of carcinogenic characters of bromate, the World Health Organization (WHO) and the United States Environmental Protection Agency (USEPA) have recommended a maximum acceptable bromate concentration of 10 μg/L (0.078 μM) (Xie et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, it is mainly used in the bread-making process to mature and improve dough (Menendez-Miranda et al 2013). Also, bromate may be added to fish paste, fermented beverages, permanent wave solutions, and hair care products (Balamurugan and Chen 2007). It has been demonstrated that bromate is linked to cancer in laboratory animals.…”
Section: Introductionmentioning
confidence: 98%
“…It was reported that bromate ion can cause renal cell tumors [2]. The International Agency for Research on Cancer has classified it as 2B carcinogen [3].…”
Section: Introductionmentioning
confidence: 99%
“…They can accept and give certain number of electrons without decomposing, giving way to mix valance species that makes them very attractive in the area of electrocatalysis. They have been studied in many electrocatalytic reductions for their use as amperometric sensors of different analytes, such as: nitrate [1][2][3][4][5][6][7], bromate [2][3][4][5][6][7][8][9][10][11][12], chlorate [13], iodate [2,8,14], and hydrogen peroxide [2][3]7,[14][15][16]. Nevertheless, their solubility limits its application in solid state electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%